Analysis of economic viability of photovoltaic systems in residential areas considering incentive policies - Muñoz Vara, Saúl; Puma Chávez, José Luis; Obispo Vásquez, Angel Eduardo; Villavicencio Gastelu, Joel (LACCEI, 2024)
In recent decades, the diffusion of residential photovoltaic systems has been observed in different countries. In most cases, this diffusion occurred because of the implementation of incentive policies. This study presents a methodology for determining economic viability by considering different incentive policies. Viability is analyzed based on economic indicators, such as NPV, IRR, Payback, and LCOE. The results indicate that the installation project of a photovoltaic system located in the city of Lima, Peru, is unviable under the current incentive conditions, resulting in an 18-year payback. However, considering more effective incentive policies made the use of PV systems viable, resulting in a payback period of up to eight years.